A comparative study on musicians and non-musicians’ affective response in music listening / Loh Wai Neng - Loh , Wai Neng (2020)
This study examined the affective responses in the music listening among undergraduates’ student using Circumplex Model of Emotion (Russell, 1980). The purpose of this study was to investigate the affective responses of undergraduate music major and non-music major students in music listening to four different music genres, which were classical music, romantic music, atonal music and experimental music. A study involving of 123 participants from undergraduate music major and non-music major students in Klang Valley area was conducted using google form. By using SPSS to tabulate the data, the result showed that there were no major differences between both musicians and non-musicians when they listen to four different types of music genres. For classical music and romantic music, emotion responses for both musicians and non-musicians are towards to high valence, whereas for atonal music and experimental music, the emotion responses for both musicians and non-musicians are towards to low valence.